Strategies to assess and promote the socio-emotional competencies of university students in the socio-educational and healthcare fields: A scoping review - Natalia Gandía-Carbonell; Cristian Molla-Esparza; Sònia Lorente; Paz Viguer; Josep-Maria Losilla (PLoS ONE, 2025)
This scoping review systematically analyses and synthesises empirical evidence on measures and intervention programmes aimed at promoting socio-emotional competencies (SECs) in university students in socio-educational and healthcare fields. A comprehensive literature search was conducted of the Scopus, PubMed, ERIC and PsycINFO databases, and a narrative synthesis approach was employed to analyse the findings from a total of 288 studies. The results highlight a general consensus on the importance of fostering SECs in university students in both fields, while revealing a significant lack of research in the socio-educational sector. Regarding both populations, a notable heterogeneity was found in the measurement of SECs and in the wide variety of tools used, which were based on different theoretical approaches, and were often not standardised or not exclusively designed to measure this type of competencies. In the intervention programmes reviewed, the SECs most frequently promoted were empathy and interpersonal emotional perception, communication, and identification, understanding, and regulation of one’s own emotions. Nonetheless, many studies lacked detailed reporting on the theoretical frameworks and intervention procedures applied, therefore limiting their replicability. Future intervention programmes should align targeted competencies with students’ profiles, future roles and professional needs, using standardised, profile-adapted measures to better evaluate their effectiveness.